The Dual Role of an Air Distribution System, Both Reducing the Concentration of Infectious Agents and Spreading Infectious Agents - Sandberg, Mats (Frontiers in Built Environment, 2022)
Ventilation removing and spreading contaminants. A large number of people becoming sick due to the COVID -19 pandemic are infected in their homes. Therefore, the spread of infectious agents, when infectious and susceptible individuals are together in their homes, is an important issue. Usually, ventilation is regarded as a process of only diluting and removing contaminants, but it is also a mechanism for spreading contaminants. The latter issue is of major importance when there is a pandemic. An air distribution system must, therefore, be viewed from a wider perspective than is generally the case. There is a need for a shift of paradigm. The scope of this study is to introduce new concepts that will make it possible to analyze air distribution systems from such a wider perspective.